Exstrophy-Epispadias Complex in a Newborn: Case Report and Review of the Literature - Enrico Valerio; Valentina Vanzo; Patrizia Zaramella; Sabrina Salvadori; Marco Castagnetti; Eugenio Baraldi (Thieme Medical Publishers, Inc., 2015)
Abstract Aim The aim of this report is to present a brief review of the current literature on the management of EEC. Case Report A term male neonate presented at birth with classic bladder exstrophy, a variant of the exstrophy-epispadias complex (EEC). The defect was covered with sterile silicon gauzes and waterproof dressing; at 72 hours of life, primary closure without osteotomy of bladder, pelvis, and abdominal wall was successfully performed. Discussion EEC incidence is approximately 2.15 per 1,00,000 live births; several urological, musculocutaneous, spinal, orthopedic, gastrointestinal, and gynecological anomalies may be associated to EEC. Initial medical management includes use of occlusive dressings to prevent air contact and dehydration of the open bladder template. Umbilical catheters should not be positioned. Surgical repair stages include initial closure of the bladder and abdominal wall with or without osteotomy, followed by epispadias repair at 6 to 12 months, and bladder neck repair around 5 years of life. Those who fail to attain continence eventually undergo bladder augmentation and placement of a catheterizable conduit. Conclusion Modern-staged repair of EEC guarantees socially acceptable urinary continence in up to 80% of cases; sexual function can be an issue in the long term, but overall quality of life can be good.